2016
DOI: 10.1177/0897190016634516
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics for the Treatment of Infantile Colic: A Systematic Review

Abstract: Supplementation with the probiotic L. reuteri in breastfed infants appears to be safe and effective for the management of infantile colic. Further research is needed to determine the role of probiotics in infants who are formula-fed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 14 publications
0
52
0
3
Order By: Relevance
“…Biogaia ProTectis contains a single strain of L. reuteri (the same strain described in the meta-analysis) 22 , is available as a liquid drop either with or without added Vitamin D, and has been shown in several studies of term infants to decrease colic. 110 An alternative would be to encourage the motivated parents to take a probiotic product themselves in hopes of transmitting the desired microbes to their infant. 111 …”
Section: Which Probiotic To Prevent Nec?mentioning
confidence: 99%
“…Biogaia ProTectis contains a single strain of L. reuteri (the same strain described in the meta-analysis) 22 , is available as a liquid drop either with or without added Vitamin D, and has been shown in several studies of term infants to decrease colic. 110 An alternative would be to encourage the motivated parents to take a probiotic product themselves in hopes of transmitting the desired microbes to their infant. 111 …”
Section: Which Probiotic To Prevent Nec?mentioning
confidence: 99%
“…It has been hypothesized that perinatal manipulation of gut microbiota by probiotics supplementation can result in a decrease of gastrointestinal functional symptoms [6]. …”
Section: Introductionmentioning
confidence: 99%
“…One of the most promising new advances in the management of infant colic is using probiotics to modulate the gut microbiota, especially Lactobacillus reuteri (DSM 17938), which has been proven to be effective in breast-fed infants with colic (8). However, it is intriguing that the largest trial so far, and the only study to include formula-fed infants, is the only one that has showed Lactobacillus reuteri to be ineffective in treating colic (9).…”
Section: Infant Colic Is Still a Mysterious Disorder Of The Microbiotmentioning
confidence: 96%